FORMULATION FLAKES CEREAL OF LOTUS (Nelumbo nucifera) AND SEAWEED (Eucheumma cottoni) AS FUNCTIONAL FOOD - Ridhowati, Sherly; Rohmania, Ainur; Rinto, Rinto; Nugroho, Gama Dian; Pitayati, Puspa Ayu; Rachmawati, Siti Hanggita; Baehaki, Ace; Pangawikan, Aldila Din (Jurnal Perikanan Unram, 2025)
The swamp waters in Indonesia are dominated by lotus plants, especially lotus seeds which are abundant but limited in processing. This study aimed to determine formulation flakes cereal from the composition of lotus seed (Nelumbo nucifera) and seaweed (Eucheumma cottoni) flour as functional food. This research was carried out in a laboratory experiment using the Completely Randomized Design (CRD) method with 4 treatment (100% tapioca; 50% tapioca, 20% lotus, 30% seaweed; 20% tapioca, 30% lotus, 50% seaweed, and 30% tapioca, 50% lotus, 20% seaweed) with 3 replications.The parameters were consisted of chemical analysis (moisture content, ash, fat, protein, carbohydrates, and crude fiber ), physical (water absorpsion and solubily index), and sensory. The results have showed that the moisture (3.13% - 3.61%), ash (1.03% - 8.25%), fat (8.38% - 9.19%), protein (1.45% - 10.96%), carbohydrates (67.69% - 86.71%), crude fiber (1.08% - 5.73%). For the water absorpsion index has ranged from 11 g/g to 5,07 g/g. and water solubily index levels ranged from 0,017g/mL to 0,057g/mL. While the sensory analysis showed a significant effect on the value of aroma and color, but not a significant effect on the value of taste and texture.